Efektifitas Terapi Akupresur Terhadap Peningkatan Kualitas Tidur pada Pasien dengan Cardiovaskular Disease: Tinjauan Sistematis - Hasdi Hasdi; Natalia Somalangi; Elly Lilianty Sjattar; Abdul Majid (Politeknik Kesehatan Kemenkes Mamuju, 2022)
Cardiovascular Disease (CVD) is a disease with the highest morbidity and mortality in the world today. Short sleep duration and poor sleep quality are associated with CVD incidence. Acupressure therapy is an alternative to improve sleep quality. The purpose of this review is to evaluate the effectiveness of acupressure therapy on improving the sleep quality of CVD patients. Method of the literature review follows PRISMA model. Data were retrieved through PubMED, ProQUEST, Science Direct, CINHAL, Wiley Online Library, Cochrane Library, Google Schoolar from 2016-2021 by using keywords: cardiovascular disease, quality of sleep, acupressure. The inclusions were full paper, In English language. The results showed six research articles: 4 articles reporting the RCT method and 2 articles using the Quasy Experiment method. The results of the study showed that acupressure therapy with a dose once a day for 2 minutes was effective in improving the sleep quality of CVD patients (score: 14-23) even though it was carried out with different variations and techniques in the procedure (p=0,00-0,05). The conclusion of this study shows that acupressure therapy has a positive impact on improving the sleep quality of CVD patients even though it is carried out with different variations and techniques.